Aplikasi Remote Sensing dan Geographic Information System untuk Pemetaan Potensi Sumberdaya Wilayah Penunjang Pariwisata di Kawasan Penatih Kota Denpasar - LESTARIANI, A.A. INTANG PUJA; LANYA, INDAYATI; KUSMIYARTI, TATI BUDI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.7, No.1, Januari 2018, 2018)
Remote Sensing and GIS Applications to Support Regional Resource Potential Mapping Tourism in Region Penatih Denpasar City Government programs to increase regional development by promoting the potential of the whole village are being improved. The development is intended to utilize the space and resources to support optimal in public life in accordance with the objectives and the expected goals. Penatih village is an area designated as rural tourism in 1995, but until recently there has been also developed. In support of tourism development in the region, information regarding potential in Penatih attraction needs in the review. In this era of globalization is indispensable information technology based both regions and potential. This study aims to assist the government in development in the village Penatih with the information potential of tourism in the region. The technology can be used to inform potential of tourism in the region Penatih that is Penatih Remote Sensing and Geographic Information System (GIS). The results obtained from this research in the form of maps are Subak map, Village map, Agro Tourism map, Culture Tourism Potential map and Tourism map in Coach Area.